Educação na cibercultura: a vida acadêmica na palma da mão no app ITOP - Sá , Welinton Alves de (Universidade Federal do Tocantins, 2022)
This paper consists of a report that presents the research process and the resulting educational product, carried out within the scope of UFT's Professional Master in Education (PPPGE). We are immersed in the cyberculture movements, educational institutions, especially private ones, are being called to think more distance learning options, online classes, students have less time and, in this context, think interaction strategies, Learning and ease for academic life becomes imperative. In this sense, the objective of this work was to develop a research for the construction of an information application, interaction and facilitator of the teaching / learning process for the ITOP college in Palmas-TO. We seek to put together in this same application tools that students could access both teaching activities, information about their course, college, and problem solving, all at your fingertips. We assumed that the reality of the institution and its students needed something that promoted learning possibilities beyond the classroom, interaction, and ways to solve administrative problems quickly and objectively. Thus, the research, exploratory and descriptive, had as data collection techniques bibliographic research, questionnaires with open and closed questions and interview. We raised the profile of college students and their consumption of digital technologies to anchor us in building the app. We also conducted an interview with the college board to understand the main communication needs with the students and the institution's pedagogical proposal, especially with regard to extending the teaching process beyond the formal class schedule. . The survey found a profile of youths who have access to the internet, who consume digital technology products and who are interested in making their lives easier through them. It also identified that the internet access provided by the ITOP Faculty satisfactorily contributes to the use of ICTs of these students. The final product, resulting from the research, was the ITOP channel application, with software fully adaptable to the most varied forms of hardware and systems agglutinator of the institution in a single platform, capable of allowing students to continue their studies in a virtual environment.